The Suicide Club - Graham, Toni (Book collections on Project MUSE., 2015)
"The people in these eight interlaced stories are 'bound together by the worst sort of grief, ' the kind that can devour you after someone close takes his or her own life. Wednesday evenings in Hope Springs, Oklahoma, offer the usual middle American options: TV, rec league sports, eating out, and church. For Slater, Holly, and SueAnn, it is the night their suicide survivors group meets. They once felt little else in common, aside from a curiosity about Jane, the group facilitator, but now they understand how deeply they need each other"--Provided by publisher.